Dutch population structure across space, time and GWAS design - Ross P. Byrne (Nature Portfolio, 2020)
Genetic variation in modern humans can reveal information about a population’s history and migration patterns. Here, the authors describe the ancestry and geospatial genetic structure of the Netherlands, and demonstrate the utility of haplotype-based covariates in genome-wide association studies.